Clinical and Genetic Characteristics and Outcome in Patients with Neonatal Diabetes Mellitus from a Low Middle-income Country - Ishara Minuri Kumarasiri; Thabitha Jebaseeli Hoole; Manimel Wadu Akila Nimanthi; Imalka Jayasundara; Reha Balasubramaniam; Navoda Atapattu (JCRPE)
Neonatal diabetes mellitus (NDM) is a disorder characterized by persistent, severe hyperglycemia presenting during the first six months of life. These disorders are rare and the incidence is approximately 1 in 90,000 live births. The aim was to describe the clinical presentation, molecular genetics and outcome of patients with NDM from a single paediatric endocrine center from a low-middle income country, Sri Lanka. A retrospective study was conducted on patients diagnosed with NDM. Medical records were reviewed for demographic data and data on clinical, biochemical and genetic analysis. The majority (96%) who underwent mutation analysis had pathogenic genetic mutations on Sanger sequencing. Permanent NDM (PNDM) was diagnosed in 19 patients with three having a syndromic diagnosis. The most common mutation was in KCNJ11. The majority of patients with PNDM (63%) presented with severe diabetic ketoacidosis. All patients with Transient NDM remitted by six months of age. Nearly half (47%) with PNDM were switched to sulfonylurea therapy with good glycemic control (glycosylated haemoglobin A1c ranged 6-7.5%). Data from the Sri Lankan cohort is comparable with other populations. The majority of cases are due to KCNJ11 mutations resulting in PNDM.